Pengaruh Current Ratio, Debt To Equity Ratio dan Return On Assets dan Terhadap Return Saham pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Wahyudil Khotib, Wahyudil Khotib; Zulpa Adila, Zulpa Adila; Renol Elmi Krisito, Renol Elmi Krisito; Mukhklis Yunus, Mukhklis Yunus (Jurnal Economic Resource, 2025)
This study aims to examine the effects of Current Ratio, Debt to Equity Ratio, and Return on Assets on stock returns of energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach is employed using secondary data from audited annual financial statements, analyzed through multiple linear regression. The results indicate that the Current Ratio has a negative effect on stock returns, the Debt to Equity Ratio has no significant effect, while Return on Assets has a positive and dominant influence. These findings highlight the critical role of profitability in shaping stock returns in the energy sector.